Fate of volcanic ash: Aggregation and fallout - Rose, William I.; Durant, Adam J. (Geology, 2011)
While suspended in Earth's atmosphere, fine ash influences radiative transfer, weather, and climate (e.g., Newhall and Self, 1982). Sulfate aerosol, also in volcanic ash clouds, dominates atmospheric effects, having stratospheric residence times of months to years (Robock, 2000), so large eruptions may have widespread consequences (Robock et al., 2009). During the eruptions in Iceland (Eyjafjallajökull in 2010, and Grimsvötn in 2011), and Chile (Puyehue-Cordon Caulle in 2011), operational ash-cloud forecast models have over-estimated far-field atmospheric ash concentrations compared to aircraft and satellite observations (Schumann et al., 2011; Stohl et al., 2011). These models do not account for fine-ash (<63 μm) particle aggregation, which results in under-prediction of proximal fine-ash sedimentation and over-prediction of distal (hundreds to thousands of kilometers) fine-ash sedimentation. This oversight can result in the closure of airspace, that would otherwise be safe.